2010
DOI: 10.1021/ja106114q
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium-Catalyzed Asymmetric Arylation of N-Tosyl Ketimines

Abstract: A rhodium-catalyzed addition of sodium tetraarylborates to N-tosyl ketimines is described. Highly efficient asymmetric catalysis has been achieved by employing a chiral diene ligand, constructing chiral amine derivatives possessing α-tetrasubstituted carbon stereocenters with high enantioselectivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
39
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(41 citation statements)
references
References 57 publications
0
39
0
2
Order By: Relevance
“…[126] Avery different chemocatalytic strategy towards optically active amines involves the addition of C-nucleophiles to imines.T his includes aw ide range of nucleophiles as demonstrated by Charette (alkyl nucleophiles), [127] Carreira (alkynes), [128] Aponick (alkynes), [129] Knochel (alkynes), [130] Shibasaki (allyl), [131] and Hayashi (allyl). [132] More recently,c hiral diarylmethylamines can be obtained through desymmetrization of prochiral diarylmethylamines,a sd emonstrated in pioneering work by Yu. [133] An additional strategy relies on the use of Pd-or Ircatalysts [134] to conduct enantioselective allylation reactions (cf.S ection 3.3).…”
Section: Reviewsmentioning
confidence: 99%
“…[126] Avery different chemocatalytic strategy towards optically active amines involves the addition of C-nucleophiles to imines.T his includes aw ide range of nucleophiles as demonstrated by Charette (alkyl nucleophiles), [127] Carreira (alkynes), [128] Aponick (alkynes), [129] Knochel (alkynes), [130] Shibasaki (allyl), [131] and Hayashi (allyl). [132] More recently,c hiral diarylmethylamines can be obtained through desymmetrization of prochiral diarylmethylamines,a sd emonstrated in pioneering work by Yu. [133] An additional strategy relies on the use of Pd-or Ircatalysts [134] to conduct enantioselective allylation reactions (cf.S ection 3.3).…”
Section: Reviewsmentioning
confidence: 99%
“…Shintani, Hayashi, et al reported the catalytic asymmetric arylation of acyclic N-sulfonyl ketimines through the use of Rh/chiral diene 65 catalysis. 41,42 For N-tosyl (N-Ts) ketimines, the reactions generally proceeded in a highly enantioselective manner at 60°C with sodium tetraarylborates 46 as arylating agents (Scheme 14). A drawback of this catalytic system was the sacrificial use of three aryl groups from 46.…”
Section: Acyclic or C=n Exocyclic Ketimines Without An α-Electron-witmentioning
confidence: 99%
“…[20,21] This latter method, developed by Ruano et al, is generally considered the most reliable method for the synthesis of N-sulfonyl ketimines. [13,14,[22][23][24] Although trustworthy, the method has some significant drawbacks. It involves the handling of peracids and peroxy compounds and is time consuming, since it requires several synthetic operations such as: 1) the preparation of the sulfinamide (only the chiral molecule is commercially available) 2) the condensation with the corresponding ketone, requiring 36 h of reflux, and finally 3) the oxidation of the N-sulfinyl imine with MCPBA.…”
Section: Introductionmentioning
confidence: 99%